Vancomycin drug resistance, an emerging threat to animal and public health - Aqib, Amjad Islam; Alsayeqh, Abdullah F. (Frontiers in Veterinary Science, 2022)
The need to supply quality food for the growing human population has led to the revolutionization of food production and processing in recent years. Meanwhile, food production sources are at risk of microbial attack, while the use of antibiotics to counter them is posing another threat to food safety and security. Vancomycin was used as the first line of defense against multiple drug-resistant bacteria salient of which is methicillin-resistant S. aureus. The emergence of the vancomycin resistance gene in bacteria impairs the efficacy of antibiotics on the one hand while its harmful residues impart food safety concerns on the other. Currently, a novel set of resistance genes “Van cluster” is circulating in a wider range of bacteria. Considerable economic losses in terms of low production and food safety are associated with this emerging resistance. The current review focuses on the emergence of vancomycin resistance and its impact on food safety. The review proposes the need for further research on the probable routes, mechanisms, and implications of vancomycin resistance from animals to humans and vice versa.